A Problem in Discounted Cash Flow. - Goetz, Billy E. (The Accounting Review, 1971)
Teachers of accounting, finance, or engineering economy may wish to devise problems that will lead their students to explore one of the pitfalls of internal rate of return or discounted cash flows. It is often suggested that alternative investment opportunities be listed in the descending order of their rates of return. This involves estimating the magnitudes and dates of expected cash receipts and disbursements, and calculating the compound discount rate which would make the net present worth of such future flows equal to the initial outlay. For example, the internal rate of return required to make this a break-even project is based on certain given details. These details include an initial cash outlay at T 0 $100,000. It also includes a net cash receipts at the end of one year at T 1 of $360,000. The method described in the article is applicable to whatever discount rates and however many discount rates, one may find interesting. It is expected that executives will use it to solve real capital investment problems. But it does represent a potential pitfall for some analytic approaches to real problems.